10 Stent sizing using optical coherence tomography imaging. (6th October 2022) - Rai, H; Räber, L; Leister, DM; Nef, H; Alfonso, F; Byrne, RA; Kastrati, A; Joner, M
Abstract : Introduction: Optical coherence tomography (OCT) aided pre-procedural measurement of lumen and vessel dimensions has the potential to enhance accurate stent sizing and improve clinical outcomes. We aimed to investigate the impact of stent sizing as per the criteria used in the ILUMIEN IV randomized trial in unselected patients undergoing coronary stenting at high volume tertiary care centres. Our secondary objective was to test if correct stent sizing also associates with lower incidence of follow-up major adverse cardiovascular events (MACE) in unselected real-world cohorts Methods: All consecutive lesions (and cases) undergoing pre-PCI OCT in native coronary arteries (with significant, de-novo/restenotic, obstructive lesions requiring stenting) and received stent/stents between 2012 to 2018 at 5 high volume European centres were retrospectively included. Sizing analysis was performed as per the criteria used in the ILUMIEN IV randomized trial. Ideal stent size was determined from the algorithm and compared with the stent size implanted. MACE during follow-up was defined as a composite of all-cause death, myocardial Infarction, target lesion revascularization and stent thrombosis. Results: A total of 178 patients were include with 193 treated lesions. Mean age was 65.1±11.2 years, 82.6% were male. A total of 11.8% of the included lesions were restenotic, 21.2% had a major bifurcation, while 26.4% had moderate to severe calcification; 63.7% of treated lesions were complex in nature (type B2/C). Mean number of stents/scaffolds implanted per lesion was 1.16±0.43. A total of 86.0% of lesions were stented with conventional drug eluting stents, 13.0% were stented with bioresorbable vascular/resorbable magnesium scaffolds. Maximum stent/scaffold diameter used was 3 (3.00, 3.50) mm while total stented length was 15 (15, 24) mm. Stent overlap was observed in 18.1% of lesions and 60.1% of lesions received post-dilation. 138 (71.5%) lesions also had post-intervention OCT available for stent expansion index (SEI) assessment. Amongst 193 lesions analysed for sizing: 78 (40.4%) lesions were correctly sized for stents; 68 (35.2%) lesions were undersized; 47 (24.4%) lesions were oversized. SEI was marginally higher in correctly/oversized lesions as compared to the undersized lesions (0.78±0.13 vs. 0.77±0.10, p= 0.69). At a median of 604 (234, 1, 098) days MACE incidence in correctly sized group was 7.7%, in undersized group was 10.3% and in oversized group was 16.7%. Kaplan-Meier plots for cumulative MACE free log survival in three sizing groups is displayed as figure 1 . Conclusions: The present real-world data highlights the fact that less than half of treated lesions are being correctly sized for stents during PCIs. MACE-free survival during follow-up of correctly sized lesions seem to be marginally better highlight the potential impact of OCT based correct sizing during PCI. This warrants further investigations with larger unselected cohorts in order to establish a definitive benefit in terms of event reduction during post PCI follow-up.